Relationship between Fracture of the Ulnar Styloid Process and DRUJ Instability: A Biomechanical Study - Nakamura, Toshiyasu; Moy, Owen J.; Peimer, Clayton A. (Journal of Wrist Surgery, 2020)
Background There has been clinical question in the treatment of ulnar styloid fracture with distal radius fracture, surgical fixation of the styloid fragment, or ignorance of the fragment. We examined relationship between size of the ulnar styloid fracture and distal radioulnar joint (DRUJ) stability biomechanically to answer the above clinical question.Methods Changes in the dorsopalmar stiffness of the DRUJ after experimentally simulating in four types of ulnar styloid fractures were examined in cadavers. After tip, middle, base-horizontal, and base-oblique type of styloid fractures were made sequentially, changes in dorsopalmar DRUJ stiffness were measured using the MTS machine in the intact wrist, for each fracture, at 60 degrees pronation, neutral, and 60 degrees supination, respectively. Additional cutting of the radioulnar ligament (RUL) at the fovea was also simulated with the base-horizontal fracture.Results The tip and middle type fractures did not demonstrate significant loss of stiffness compared with the intact. The base-horizontal fracture demonstrated only significant loss of stiffness in the dorsal direction (radius palmar; ulnar dorsal) with forearm in neutral rotation. The base-oblique fracture demonstrated significant loss of dorsopalmar stiffness of the DRUJ. Additional section of the RUL with the base-horizontal fracture induced significant loss of stiffness of the DRUJ compared with the intact.Conclusions Because the RUL originates from the fovea as well as from the base of the ulnar styloid, these results suggest that DRUJ instability closely correlates with how much of the bony fragment includes the originating portions of the RUL. The findings further suggest that larger base-oblique and base-horizontal fragments with resultant DRUJ instability must be reattached, but that even base-horizontal fragment as well as tip and middle ulnar styloid fragment can be ignored when there is no instability.
Keywords: ulnar styloid; fracture; radioulnar ligament; distal radioulnar joint instability